2015
DOI: 10.1016/j.jalz.2015.05.018
|View full text |Cite
|
Sign up to set email alerts
|

[18F]flutemetamol amyloid positron emission tomography in preclinical and symptomatic Alzheimer's disease: Specific detection of advanced phases of amyloid‐β pathology

Abstract: [(18)F]flutemetamol amyloid PET detects primarily advanced stages of Aβ pathology in preclinical and symptomatic AD cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
119
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(131 citation statements)
references
References 38 publications
10
119
0
2
Order By: Relevance
“…Above the Aβ threshold, we found tau-associated hypometabolism in regions commonly used as FDG biomarker readouts for AD. Our finding of tau-related increasing metabolism in subjects with sub-threshold Aβ is consistent with postmortem-PET correlations showing that Aβ is evident in a subset of individuals below typical PET thresholds 37, 38 .…”
Section: Discussionsupporting
confidence: 90%
“…Above the Aβ threshold, we found tau-associated hypometabolism in regions commonly used as FDG biomarker readouts for AD. Our finding of tau-related increasing metabolism in subjects with sub-threshold Aβ is consistent with postmortem-PET correlations showing that Aβ is evident in a subset of individuals below typical PET thresholds 37, 38 .…”
Section: Discussionsupporting
confidence: 90%
“…The probability of a positive PET image interpretation in this study was 50% in the sparse category, suggesting that this may be possible, but it seems likely that analysis of other regions, such as the striatum or, better yet, a measurable, reliable quantification method, would likely improve the lower detection limit, enabling assessment of β-amyloid in preclinical AD, a stage of disease almost certainly more amenable to preventative treatment strategies or disease-modifying therapeutics. In this context, it is necessary to note that recent studies reported that amyloid PET only detects cases with already advanced amyloid phases (3 and higher) whereas initial phases (1 and 2) could not be identified with [ 18 F]flutemetamol or [ 11 C]PIB [45, 55]. Conversely, increasing the sensitivity of PET β-amyloid scans may decrease the specificity to predict clinically significant AD neuropathology.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these data do not support the hypothesis that the biomarker construct of SNAP is analogous to the post-mortem construct of primary age-related tauopathy (PART) 10 . Approximately 42% of the sample described by Crary et al (182/434) would, if they had undergone Amyloid PET, likely be classified as Aβ − because they were Thal Aβ Phase 0–2 35 . Of these 182 Aβ − cases, 77 (42%) were Braak Stage III or IV, were age~90, and MMSE~23 10 .…”
Section: Discussionmentioning
confidence: 99%